NATIVE PLATINUM IN ROMANIA: THE SINGLE OCCURRENCE – PIANU VALLEY, SEBEŞ MTS. (PANGEEA, 2025)
Known as an important occurrence of gold, at Pianu native platinum has been also found as early as 1855. The platinum contains also Fe (about 9%), a common fact for platinum occurrences. As a source for platinum the ultrabasic rocks (most serpentinites) have been considered, widely distributed in the Sebeş Mts., however not direclty occurring in the catchment area of the Pianu Valley.
Keywords: native platinum; alluvial deposits; Pianu Valley; Sebeş Mts.; Romania